The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/1350650119894167
|View full text |Cite
|
Sign up to set email alerts
|

Computational investigation on the performance of hydrodynamic micro-textured journal bearing lubricated with micropolar fluid using mass-conserving numerical approach

Abstract: The tribological characteristic of journal bearing systems can be enhanced with the integrating of textures in the contact interfaces, or using the lubricating effect of non-Newtonian fluids. In this study, the combined effects of bearing surface texturing and non-Newtonian lubricants behavior, using micropolar fluid model, on static characteristics of hydrodynamic circular journal bearings of finite length are highlighted. The modified Reynolds equation of micropolar lubrication theory is solved usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 81 publications
1
17
0
Order By: Relevance
“…In summary, the performance of the bearing is improved by adjusting the distribution position of the micro-textured. This confirms the findings of Manser et al (2020a, 2020b), Sharma et al (2019) and Tala-Ighil and Fillon (2015) that there are differences in the optimal location of the micro-textured due to different structural parameters and operating conditions of the bearings. In this paper, bearing performance is improved when the textured is located in the maximum pressure area.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In summary, the performance of the bearing is improved by adjusting the distribution position of the micro-textured. This confirms the findings of Manser et al (2020a, 2020b), Sharma et al (2019) and Tala-Ighil and Fillon (2015) that there are differences in the optimal location of the micro-textured due to different structural parameters and operating conditions of the bearings. In this paper, bearing performance is improved when the textured is located in the maximum pressure area.…”
Section: Resultssupporting
confidence: 88%
“…Researchers have investigated several methods to improve the performance of bearings from bearing structure, fluid media and active control (Sawano et al, 2015;Manser et al, 2020aManser et al, , 2020bRehman et al, 2021). Surface micro-textured technology is considered to be an effective method to improve the lubrication performance of friction surfaces (Yang et al, 2020;Zhang and Bijay, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [9] revealed that the provision of a texture in the form of a convex-concave spherical texture configuration on the bearing surface was able to significantly reduce the friction coefficient. An interesting finding was reported by Manser et al [10] who found that by combining the effects of micro-texturing and micro-polar non-Newtonian lubricant, an enhancement load support but low friction of journal bearing was achieved. In recent lubrication, Saleh et al [11] revealed that to get a high load-support, a convex texture with a perpendicular direction of curvature was recommended.…”
Section: Introductionmentioning
confidence: 65%
“…For a single layer porous bearing, they found better performance when the mass flow rate is reduced by 40% in comparison with Newtonian fluid. Manser et al (2020) highlighted the enhancement in the performance of textured journal bearing with micropolar lubricant, especially at higher eccentricity.…”
Section: Introductionmentioning
confidence: 92%